(untitled) (The New Uzbekistan Journal of Medicine, 2025)
The presence of sperm was checked in 50 objects (smear and tampons) received from the morphology and ambulatory department of the forensic biology laboratory of the Surkhandarya Branch of the Republican Forensic Scientific and Practical Center of Forensic Expertise. In the study, the titer of potato juice should be 1:32 in physiological solution, the presence of sperm prevents the start of “potato” agglutination, that is, it depends on the delayed reaction of agglutination. In our study, no agglutination and absorption were observed in the controls.